An analytical study of the vitality of the conscience of the senior leaderships in the boards of colleges and departments of physical education and sports science in Baghdad - مروة علاء حسين أ.م.د سندس موسى جواد (physical education and sport sciences college for women/ Baghdad University, 2020)
The problem of research lies in answering some of the question: What is the reality of (vital conscience) in some colleges and departments of physical education and sports science in Baghdad from the viewpoint of the teachers? And The aim of the research is to prepare a scale (the vitality of the conscience) and learn about its reality in colleges and departments of physical education and sports science in Baghdad from the viewpoint of teachers and The researcher relied on the descriptive method in the survey method and the relationships related to the nature of the research problem and The sample of the research was senior administrators teaching some colleges and departments of physical education and sports science in Baghdad , Through the results of the research, the researcher assumed that the faculty members in some colleges and departments of physical education and sports science enjoy a high degree of (vital conscience) and Through the results of the research, the researcher recommends paying attention to the higher departments, subordinates, teaching staff and qualified academic cadres who possess the characteristics and characteristics of (vital conscience) to benefit from them in achieving the requirements and goals of the higher departments and to reach the best results.